Analisis Komparatif Kadar Flavonoid Centella asiatica Berdasarkan Variasi Pelarut Ekstraksi: Tinjauan Sistematis - Fitri Elizabrth Hasibuan (Jurnal Bioleuser, 2026)
Centella asiatica (L.) Urb. is a medicinal plant rich in bioactive compounds, particularly flavonoids, which contribute significantly to its antioxidant activity. The extraction efficiency of flavonoids is strongly influenced by the type of solvent used during the extraction process. This study aimed to evaluate the effect of extraction solvent variation on the total flavonoid content (TFC) of C. asiatica (L.) Urb through a systematic review approach. A comprehensive literature search was conducted across six electronic databases covering publications from 2015 to 2025. Study selection was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A total of six eligible studies met the inclusion criteria and were included in the review, yielding 18 extraction datasets. The extracted information included solvent type, extraction method, analytical technique, and TFC expressed as mg quercetin equivalent per gram (mg QE/g). The results demonstrated that the TFC of C. asiatica (L.) Urb ranged from 1.89 to 48.43 mg QE/g. Ethyl acetate produced the highest TFC (48.43 mg QE/g), followed by ethanol (26.66–31.63 mg QE/g), whereas water yielded comparatively lower TFC values (7.26–9.33 mg QE/g). These findings indicate that semi-polar solvents are more effective than highly polar solvents in extracting flavonoids from C. asiatica (L.) Urb. In addition to solvent type, solvent concentration and analytical methods were identified as contributing factors to the variability of TFC reported among studies. Therefore, the selection of an appropriate extraction solvent is crucial for maximizing the recovery of flavonoids from C. asiatica (L.) Urb.